PENGARUH E-SERVICE QUALITY TERHADAP E-LOYALTY MELALUI E-SATISFACTION (STUDI PADA PELANGGAN TOKO ONLINE SHOPEE DI KOTA MEDAN): PENGARUH E-SERVICE QUALITY TERHADAP E-LOYALTY MELALUI E-SATISFACTION (STUDI PADA PELANGGAN TOKO ONLINE SHOPEE DI KOTA MEDAN) - Megasari Gusandra Saragih (Institute of Computer Science (IOCS), 2019)
The research objective is to analyze the results of e-quality services for e-loyalty through customer e-satisfaction at Shopee's online store in Medan City. The study was conducted in Medan City on 135 Shopee store customers online. The analytical tool used is Structural Equation Modeling (SEM) with AMOS assistance. This study found that e-service quality had a significant effect on e-satisfaction and e-loyalty, satisfaction had significant effect on e-loyalty, and satisfaction-satisfaction mediated partial mediation between e-service quality and e-loyalty.